Analyzing Difficulty Index of Ekadanta English Section Multiple Choice - Yusnida, Dara; Ayouni, Nour (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Evaluation has been an essential component of the teaching and learning process for as long as it has been a part of the teaching and learning process itself, which is something that takes place all the time at every educational institution. This is because the assessment has a tight link with educators in the process of transferring information to analyze how much students' abilities have developed over the course of the learning process and while assembling each assignment in the process of learning. This study tries to shed light on the index of difficulty index found in a set of prediction test in Ekadanta tutoring book. This study employed descriptive qualitative approach. The data source was 20 questions from Ekadanta tutoring book. The subject of this study were 11 students of English Department at Universitas Iskandarmuda, Banda Aceh, Indonesia. The data collection was carried out by instructing the students to do the test within 40 minutes. After the data obtained, they were analyzed using index of difficulty formula and categorized into its index level. The results shows that from 20 question, there are 8 questions fall under difficult index, 8 questions are categorized into moderate, and the other 4 questions are considered easy in the level of difficulty index. It is concluded that the test is good and descent from the perspective of the difficulty index. It is later suggested that future research would involve more questions and test sets as well as participants in studies alike.